Abrupt climate change: Exploring the implications of a wild card. (December 2020) - Bengston, David N.; Crabtree, Jason; Hujala, Teppo
Highlights: Abrupt climate change has occurred many times in the paleoclimatic record. The Implications Wheel® method was used to identify and evaluate possible implications of rapid climate change. Strategies to increase resilience are critical given the likelihood of disruptive impacts. Early warning signals for abrupt climate change could be identified and closely monitored. Fundamental uncertainty suggests the importance of futures research that taps into creativity and imagination. Abstract: Anthropogenic climate change has been gradual to date, but if climate tipping points are crossed the pace of change could accelerate significantly. This study explores possible implications of abrupt climate change, with a partial focus on implications for forestry. We used the Implications Wheel® participatory futures method to identify and evaluate direct and indirect, positive and negative implications of rapid change in the climate system. A large number of possible implications were generated, including a wide range of social, economic, and ecological costs and benefits. Participants identified many "likely strong negative" implications that were scored as both highly likely and strongly negative. A key conclusion of this study is the importance of developing strategies to increase social and ecological resilience given the likelihood of highly disruptive impacts of abrupt climate change. A second conclusion is the need to identify early warning signals for abrupt climate change and closely monitor those signals. Finally, the fundamental uncertainty about abrupt climate change suggests the importance of futures research that taps into creativity and imagination. Our inaction in the face of climate change has been characterized as a failure of imagination, an inability to envision a different and sustainable world, and so futures thinking and methods that encourage creative thinking have an important role in addressing the "inevitable surprise" of abrupt climate change.